Trends of strong opioid consumption in Malaysia and other Southeast Asian countries from 2005 to 2014 - Zin, Che Suraya (2017)
Background and aims It was reported that opioid consumption in developing countries was stagnated or decreased but precise data on the consumption are unclear. This study examined the trends and patterns of opioid consumption in Malaysia and other Southeast Asian countries. Methods